Determine the effectiveness of digital influencers in recommending brands via an electronic word of mouth on customer attitudes - Mustafa Aldori, Mustafa Kamal (International Journal of Psychosocial Rehabilitation, 2020)
In recent years, a lot of research still is undergoing to understand how they can create a link with their supporters that will affect their attitudes and actions against endorsed products. This paper attempts to evaluate how effectively influencers of media support goods by online word of mouth can affect brand loyalty, predicted market awareness and the willingness to buy recommended items. The results of this study show the potential of media influencers to change their client’s behavior, demonstrating that their control can impact attitudes, perceptions and purchase decisions regarding recommended products. The research therefore helps administrators to understand how the marking power of forces operates. In this sense, businesses looking to involve customer products in a non-traditional marketing communication strategy are able to invest in internet influencers as a valuable online communication tool, as this capacity enhances the brand’s reputation.